Analisis Pemangku Kepentingan Dana Otonomi Khusus Aceh dengan Pendekatan Mendelow’s Matrix - Akhsanul Khalis (Indonesian Journal Publisher, 2025)
The Aceh Special Autonomy Fund (Otsus), granted after the 2005 Helsinki Agreement, was intended to accelerate development, reduce inequality, and strengthen regional governance. However, two decades of implementation reveal a paradox: despite large fiscal transfers, improvements in welfare remain limited. This study aims to analyze the dynamics of stakeholders in the management of the Aceh Otsus Fund using Mendelow’s Matrix (1991). The research relies on secondary data from policy documents, reports, and academic studies to map actors’ levels of power and interest. The findings indicate that the Aceh Provincial Government and the Aceh Regional Parliament hold both high power and interest, placing them in the Key Players quadrant. Nevertheless, weak coordination between these actors has resulted in policy–implementation gaps. Meanwhile, the Central Government and the Supreme Audit Board act mainly as supervisors, exercising significant power but with limited direct interest in implementation, which reduces local effectiveness. Civil society groups and vulnerable communities remain marginalized due to the dominance of political elites and bureaucrats. The study concludes that strengthening transparency, enhancing community participation, and improving communication among stakeholders are critical for better fund management. Future research should adopt mixed-method approaches and conduct comparative studies with other autonomy regions to enrich analysis and policy recommendations.